Shelf‐Life Extension of Chill‐Stored Beef Longissimus Steaks Packaged under Modified Atmospheres with 50% O2 and 40% CO2. Issue 7 (30th May 2016) - Yang, Xiaoyin; Niu, Lebao; Zhu, Lixian; Liang, Rongrong; Zhang, Yimin; Luo, Xin
Abstract: This study was conducted to compare the shelf‐life of beef steaks stored in different packaging conditions: overwrapped (OW) packaging and 2 modified atmosphere packaging systems (MAP): 80% O2 MAP (80% O2 /20% CO2 ) and 50% O2 MAP (50% O2 /40% CO2 /10% N2 ). Steaks were stored at 2 °C for 20 d. Headspace gas composition, microbial counts, color stability, pH, purge loss, and lipid oxidation were monitored. Among the packaging types, 50% O2 MAP was superior to OW packaging and 80% O2 MAP in delaying bacterial growth and extending shelf‐life to 20 d. 50% O2 MAP also gave steaks an acceptable color during storage. No significant differences were observed in color stability of steaks packaged in both 50% O2 MAP and 80% O2 MAP. This study reveals 50% O2 MAP is a realistic alternative to preserve beef steaks efficiently.